The Effectiveness of Some Types of Refugia for Supplying the Population of The First Lice (Bemisia Tabaci) on Soybean Plant - Juniaty Arruan Bulawan; La Mpia; Muslimin Sepe; Erik Hardiana (Jurnal Biologi Tropis, 2023)
Soybean is one of the important food commodities in Indonesia which occupies the third position after rice and corn. In 2020, soybean production reached 632.3 tons but decreased by 3.01% to 613.3 tons in 2021 and is predicted to continue to decline until 2024. Whitefly (Bemisia tabaci) is one of the important pests on soybeans. which is also a viral vector. The purpose of this study was to obtain refugia plants which were effective in suppressing the whitefly pest population on soybeans. The study was carried out using a Randomized Block Design (RAK) with 5 treatments and repeated 3 times so that there were 15 experimental units. The treatment used 4 types of refugia plants, namely: R1 = yellow kenikir flower, R2 = orange kenikir flower, R3 = Zinnia elegans paper flower, R4 = Tagetes erecta flower, and R0 = Control (soybean plant without refugia block). The results showed that the four types of refugia affected the whitefly pest population but were not significantly different in each treatment and had no effect on the intensity of the whitefly pest attack. There are 7 species of natural enemies of whitefly consisting of 6 species of predators and 1 species of parasitoid. Most predators come from the order Coleoptera.